Estresse e bem-estar no trabalho de enfermeiros hospitalar : proposta de promoção à saúde do trabalhador - Silveira, Eliseu de Ávila (2019)
Introduction: stress is inherent in the work of the nurse and its chronicity has a direct impact on health in the biopsychosocial aspect, besides negatively inferring in the institutions and in the quality of care provided by this professional. On the other hand, promoting well-being at work among these workers favors improvements at the individual and organizational levels. Progressive muscle relaxation is a nursing intervention that affects the individual with physiological and behavioral responses, thus, the introduction of this technology in the work environments of these professionals, becomes important and challenging, since, it allows to reflect in improvements for the institutions and individual health, as well as patient care. Objective: to evaluate the effect of the use of a relaxation protocol on the levels of stress and well-being in the work of the hospital nurses. Method: study longitudinal, prospective, of a quantitative nature that followed, during eight consecutive weeks, 16 nurses from a hospital institution who self-refer stressed at work. The protocol consisted of eight sessions of progressive muscle relaxation. Data were collected by questionnaire containing sociodemographic and professional variables; Work Stress Scale; Work Well-being Scale, upon entry into the protocol and upon its finalization. For the data analysis, the Statistical Package for Social Sciences - SPSS (version 19.0), the Shapiro-Wilk, Wilcoxon, Sperman and Mann-Whitney tests were used, with a significance level of 5%. Results: the average of the stress decreased from 60/55 (p= 0.166) and the average of the welfare factors at work: positive affect, negative affect and achievement increased from 3.22 / 3.42 (p = 0.073); 2.07 / 2.29 (p = 0.094) and 3.71 / 3.92 (p = 0.060), respectively. Product: a care protocol was developed for the promotion of worker's health with the use of progressive muscle relaxation and an instrument for evaluating the worker's health promotion program. Conclusion: the use of progressive muscle relaxation protocol provided reduced mean stress and promoted well-being at work. In addition, it is a simple, low-cost, self-enforceable and practiclable technique that demands little time from the worker for its execution and significantly impacts on the development of its work activities.